Appraisal of antivenom production in public laboratories in Latin America during the first semester of 2020: The impact of COVID-19 - Gutiérrez, José María (2021)
Snakebite envenomings remain a significant public health concern, particularly in Latin America, where a long tradition of antivenom production exists. The World Health Organization (WHO) highlights safe and effective pharmacotherapeutic treatments, including antivenoms, as a cornerstone for envenoming management. Antivenoms, derived from immunoglobulins of immunized animals, require timely availability and accessibility to reduce morbidity and mortality. In Latin America, public laboratories in countries such as Argentina, Brazil, Peru, Bolivia, Ecuador, Colombia, Venezuela, Costa Rica, and Mexico play a central role in antivenom production, coordinated through the Latin American Network of Public Antivenom Manufacturing Laboratories (RELAPA), under the Pan American Health Organization (PAHO). In 2020, a survey was conducted among RELAPA institutions to assess the impact of the COVID-19 pandemic on antivenom production from January to July. The survey evaluated production levels, demand, staffing, procurement of consumables and equipment, budget allocations, and the overall effect of pandemic-related disruptions. Findings from this assessment aim to inform strategies for sustaining and improving antivenom availability during global health emergencies.